Targeted Delivery of the Mitochondrial Target Domain of Noxa to Tumor Tissue via Synthetic Secretion System in E. coli - Lim, Daejin; Jung, Woong Chae; Jeong, Jae-Ho; Song, Miryoung (Frontiers in Bioengineering and Biotechnology, 2020)
Targeted delivery of drugs is a key aspect of the successful treatment of serious conditions such as tumors. In the pursuit of accurate delivery with high specificity and low size limit for peptide drugs, a synthetic type 3 secretion system (T3SS) has been repurposed from a native genetic system encoded in Salmonella pathogenicity island-1 (SPI-1) with no virulence effectors. Here, we tested the potential of synthetic T3SS as drug delivery machinery for peptide-based drugs owing to its modular nature. First, the genetic system for synthetic T3SS was introduced into non-native host E. coli, which was chosen for its lack of Salmonella-driven virulence factors. Next, the mitochondrial targeting domain (MTD) of Noxa was tested as a cargo protein with anti-tumor activity. To this end, the gene encoding MTD was engineered for secretion through synthetic T3SS, thereby resulting in the tagged MTD at the N-terminus. When E. coli carrying synthetic T3SS and MTD on plasmids was administered into tumor-bearing mice, MTD with a secretion tag at the N-terminus was clearly detected in the tumor tissue after induction. Also, the tumor growth and mortality of tumor-bearing animals were mitigated by the cytotoxic activity of the delivered. Thus, this work potentiates the use of biotherapeutic bacteria for the treatment of tumors by implanting a dedicated delivery system.